Ocular Myasthenia: Clinical Course and the Diagnostic Utility of Assaying Acetylcholine Receptor Antibodies. (4th July 2022) - Behbehani, Raed; Ali, Abdullah; Al-Moosa, Ashraf
ABSTRACT: Myasthenia gravis (MG) is an autoimmune disease that causes neuromuscular junction transmission defect and has a predilection for the with neuromuscular junction transmission defect and predilection for extra-ocular and eyelid muscles. Most cases of ocular MG (OMG) convert later to generalised MG (GMG). Assaying acetylcholine receptor antibodies (AchRA) has been used to diagnose MG, but the reported sensitivity in OMG is lower (50%) than in GMG. We report the clinical course and the diagnostic yield of assaying AchRA in a Kuwaiti cohort of patients with OMG. We carried out a retrospective review of 47 patients diagnosed with OMG who were tested for AchRA. Ancillary tests included the ice test, single-fibre electromyography (SFMEG), and repetitive nerve stimulation electromyography (RNS). Progression to GMG occurred in 51% of OMG patients with a mean time to progression of 12.1 months (range 4 to 20 months). AchRAs were positive in 46 of 47 cases (98%), while SFEMG was positive in 31 of 34 cases (91.1%). Older age (44.25 years versus 38 years, p < .05) and higher AchRA titre (2.0 nmol/L versus 1.27 nmol/L, p < .05) were significantly associated with conversion to GMG. We have found a high rate of AchRA seropositivity in relatively younger subjects of OMG. Higher AchRA titres and older age were associated with conversion to GMG, usually within the first 2 years.